Analisis Pengaruh Pendapatan Margin Murabahah dan Ijarah Muntahiyah Bittamlik terhadap Profitabilitas Bank Umum Syariah Di Indonesia Periode 2018-2022 - Hasibuan, Fauzul Hakin; Nursafitri, Yessi; Febrianti, Dwi Rasti; Azira, Eka Nur (Universitas Nusa Putra, 2023)
The purpose of conducting this research is to determine the effect of Margin Income of Murabahah and Ijarah Mutahiyah Bittamlik on the Profitability of Islamic Commercial Banks in Indonesia for the 2018-2022 period. The type of research in this study is descriptive quantitative. The sampling technique used in this study was a purposive sampling technique and produced a sample of 6 Islamic Commercial Banks, including PT Bank BNI Syariah, PT Bank BCA Syariah, PT Bank Syariah Mandiri, PT Bank Bukopin Syariah, PT Bank BRI Syariah, PT Bank Muamalat Indonesia from the period 2018 to 2022. The data analysis method in this study is multiple regression analysis. The results of the research that has been done show that there is a significant effect of Margin Murabahah and Ijarah Mutahiyah Bittamlik income on Profitability which is carried out simultaneously.